PM Svanidhi Scheme: A Gateway To Micro Loans For Street Vendors - Trivedi, Dr. Jigna; Soni, Dr. Bindiya (South Eastern European Journal of Public Health, 2025)
Street vending is a self-employment activity commonly associated with the informal economic sector. This activity typically involves either stationary operations at a fixed spot or mobile vending, where goods and services are sold while moving through streets. Since street vendors lack a permanent business address, they often face challenges in accessing formal financial services.Prior to the launch of the PM Svanidhi Scheme, street vendors primarily relied on informal sources such as family, friends, or fellow vendors to meet their working capital needs. The PM Svanidhi Scheme was specifically introduced to provide financial assistance to street vendors, enabling them to address their business requirements. Under this scheme, vendors can access microloans starting at ₹10,000, with a maximum limit of ₹50,000. These loans play a vital role in helping street vendors revive their businesses, particularly in the aftermath of the pandemic.An additional highlight of the scheme is the provision of cashback incentives for digital transactions, encouraging the adoption of digital payment methods. The study assess the secondary on the scheme, This study aims to analyze the benefits experienced by street vendors in Gandhinagar City under the PM Svanidhi Scheme. The study also explains the view of bankers who provided loans to the street vendors under the scheme.